Spatiotemporal mass balance trends for the Antarctic Ice Sheet, 2003-2013 - Espanol, Alba; Bamber, Jonathan (Polar Data Centre; British Antarctic Survey, Natural Environment Research Council; Cambridge, CB3 0ET, UK., 2017)
The Antarctic mass trends have been collated from a combination of different remote sensing datasets. These are trends of yearly elevation changes over Antarctica for the period 2003-2013 due to the different geophysical processes driving changes in Antarctica: ice dynamics, surface mass balance and glacio-isostatic adjustment (GIA). Net trends can be easily calculated by adding together surface and ice dynamics trends. 20 km gridded datasets have been produced for each process, per year (except the GIA solution which is time-invariant). To convert elevation to mass trends, we also provide the density fields for surface (SMB) and GIA processes used in Martin-Espanol et al (2016). These can be directly multiplied by the dh/dt. To convert dh/dt from ice dynamics, simply multiply by the density of ice. Mass smb = dh/dt smb * d surf Mass ice = dh/dt ice * d ice (not provided) Mass gia = dh/dt gia * d rock NERC grant: NE/I027401/1